Organosilanes Surface Modification of Zirconium Diboride Composite Engineering Ceramics and Its Effect on the Tribological Performance of Epoxy Composites1. Issue 4 (19th September 2015) - Yang, Xiaolei; Yu, Zhiqiang; Wu, Yicheng
Abstract : Zirconium diboride/alumina composite particles are modified by three kinds of organosilanes. The modified particles are characterized by Fourier transform infrared spectrometer, X‐ray photoelectron spectra, and transmission electron microscope. The results show that the organosilanes are successfully grafted onto the surfaces of composite particles by Al–O–Si bonds from the chemical reaction between particles and organosilanes, which makes contribution to reducing the agglomeration of particles in epoxy. The epoxy composites containing modified particles present higher tribological performances and more even distribution of the thermal flux which restrains the deterioration of the tribological properties caused by the concentration of friction heat. Abstract : Surface modification of zirconium diboride composite particles is achieved by oxygen‐bridge bonds between particles and organosilanes. Modified zirconium diboride composite particles can disperse more evenly in epoxy matrix compared to unmodified one. The epoxy composites filled with modified particles present better tribological performance.